Problem-Based Learning Strategies to Improve Students' Science Literacy in Chemistry Subjects: A Recent Literature Review - Mutia Ardila; Ekin Dwi arif Kurniawan; Alfira Julian Pratiwi; Rafidah Almira Samosir (Journal of Educational Studies in Science, Technology, Engineering, Arts and Humanities, 2025)
21st-century learning requires students to have adequate science literacy skills, especially in understanding complex and abstract chemistry materials. However, the results of international assessments show that students' science literacy skills, including in Indonesia, are still not optimal. This study aims to analyze the application of the Problem-Based Learning (PBL) model in improving science literacy in chemistry learning at the high school (SMA/MA) level. The method used is a Systematic Literature Review (SLR) by analyzing articles published between 2018 and 2024. Based on the results of the analysis, 13 articles were obtained that met the inclusion criteria. The results of the review show that the application of PBL consistently strengthens the understanding of science concepts in depth and improves students' critical thinking and problem-solving skills. This learning model not only supports academic achievement but also helps students relate the knowledge learned to real situations, thereby improving the quality of science literacy needed in today's chemistry learning.